Bio‐Inspired Bimetallic Cooperativity Through a Hydrogen Bonding Spacer in CO2 Reduction. (11th January 2023) - Zhang, Chanjuan; Gotico, Philipp; Guillot, Regis; Dragoe, Diana; Leibl, Winfried; Halime, Zakaria; Aukauloo, Ally
Abstract: At the core of carbon monoxide dehydrogenase (CODH) active site two metal ions together with hydrogen bonding scheme from amino acids orchestrate the interconversion between CO2 and CO. We have designed a molecular catalyst implementing a bimetallic iron complex with an embarked second coordination sphere with multi‐point hydrogen‐bonding interactions. We found that, when immobilized on carbon paper electrode, the dinuclear catalyst enhances up to four fold the heterogeneous CO2 reduction to CO in water with an improved selectivity and stability compared to the mononuclear analogue. Interestingly, quasi‐identical catalytic performances are obtained when one of the two iron centers was replaced by a redox inactive Zn metal, questioning the cooperative action of the two metals. Snapshots of X‐ray structures indicate that the two metalloporphyrin units tethered by a urea group is a good compromise between rigidity and flexibility to accommodate CO2 capture, activation, and reduction. Abstract : Inspired by the active site of CO dehydrogenase (CODH), a novel metalloporphyrin‐based mimic has been synthesized combining a multipoint hydrogen bond donor and a bimetallic active centre. The cooperativity between the two metal centres of the catalyst was evidenced for both homo‐ and heterobimetallic analogues leading to a significant enhancement of the catalytic performances of the heterogeneous CO2 ‐to‐CO electrocatalytic reduction in water.